Information and Education Covid-19 in Paran Padang Village, Sipirok District in 2020 - Diningsih, Ayus; Ritonga, Nefonavratilova (Universitas Aufa Royhan Di Kota Padangsidipuan, 2021)
Coronavirus Disease 2019 (COVID-19) is a new type of disease that has never been previously identified in humans. The virus that causes COVID-19 is called Sars-CoV-2. Corona viruses are zoonotic (transmitted between animals and humans). Meanwhile, the animal that is the source of transmission of COVID-19 is still unknown. Based on scientific evidence, COVID-19 can be transmitted from human to human through coughing / sneezing (droplets). People who are most at risk of contracting this disease are people who are in close contact with COVID-19 patients including those caring for COVID-19 patients. Common signs and symptoms of Covid-19 infection include symptoms of acute respiratory distress such as fever, cough and shortness of breath. The average incubation period is 5-6 days, with an incubation period of fever, cough and shortness of breath. In severe cases, Covid-19 can cause pneumonia, acute respiratory syndrome, kidney failure, and even death. This community service program aims to increase public knowledge about Covid-19 information and education in Paran Padang Village, Sipirok District and increase public awareness about healthy living habits to prevent Covid-19 transmission. The target of the extension activities is all people in Paran Padang Village, Sipirok District. The expected result of this counseling is an increase in public knowledge about Covid-19 starting from signs, symptoms, causes, diagnosis, treatment, complications and ways to prevent covid-19 by maintaining a healthy life by always washing hands with soap, always using a mask when it comes out. home, always keep your distance from others and avoid crowds.